Mechanical phenotyping of primary human skeletal stem cells in heterogeneous populations by real-time deformability cytometry - Xavier, Miguel; Rosendahl, Philipp; Herbig, Maik; Kraeter, Martin; Spencer, Daniel; Bornhaeuser, Martin; Oreffo, Richard O. C.; Morgan, Hywel; Guck, Jochen; Otto, Oliver (Integrative Biology, 2016)
Skeletal stem cells (SSCs) are a sub-population of mesenchymal stromal cells (MSCs) present in bone marrow with multipotent differentiation potential. A current unmet challenge hampering their clinical translation remains the isolation of homogeneous populations of SSCs, in vitro, with consistent regeneration and differentiation capacities. Cell stiffness has been shown to play an important role in cell separation using microfluidic techniques such as inertial focusing or deterministic lateral displacement. Here we report that the mechanical properties of SSCs, and of a surrogate human osteosarcoma cell line (MG-63), differ significantly from other cell populations found in the bone marrow. Using real-time deformability cytometry, a recently introduced method for cell mechanical characterization, we demonstrate that both MG-63 and SSCs are stiffer than the three primary leukocyte lineages (lymphocytes, monocytes and granulocytes) and also stiffer than HL-60, a human leukemic progenitor cell line. In addition, we show that SSCs form a mechanically distinct sub-population of MSCs. These results represent an important step towards finding the bio-physical fingerprint of human SSCs that will allow their label-free separation from bone marrow with significant physiological and therapeutic implications.
CRIS-Team Scopus Importer:2022-08-05